Comparison of temporal changes in established cardiovascular biomarkers after acute coronary syndrome between Caucasian and Chinese patients with diabetes mellitus. (18th May 2020) - Buljubasic, Nermina; Zhao, Wei; Cheng, Jin; Li, Huijuan; Oemrawsingh, Rohit; Akkerhuis, Martijn; Yu, Haiyi; Zhou, Lequn; Wu, Yangfeng; Boersma, Eric; Gao, Wei
Abstract: Background: Population means of conventional cardiovascular biomarkers are known to differ between ethnic groups. In this study we performed detailed comparisons in the temporal pattern of these biomarkers between Caucasian and Chinese diabetic patients with acute coronary syndrome (ACS). Methods: We studied differences in temporal changes of established cardiovascular biomarkers, including high-density lipoprotein (HDL), low-density lipoprotein (LDL), total cholesterol, cardiac Troponin T (TnT), NT-proBNP and C-reactive protein (CRP), in 48 Chinese and 48 clinically matched Caucasian patients with type 2 diabetes mellitus who were admitted for ACS. Blood samples were collected at regular time intervals during 30 days to 1 year after the index ACS. Results: In the >30 day post ACS period, mean serum levels of LDL (2.16 vs. 1.47 mmol/L; p -value <0.001), total cholesterol (4.08 vs. 3.11 mmol/L; p -value <0.001), TnT (11.0 vs. 7.76 ng/L; p -value 0.010) and CRP (2.0 vs. 0.78 mg/L; p -value <0.001) were systematically higher in Caucasian than in Chinese patients. HDL and NT-proBNP levels were similar. Conclusions: Our study showed clinically relevant differences in levels of established cardiovascular biomarkers between Caucasian and Chinese post ACS patients. Further cross-ethnic studies are warranted to determine secondary prevention treatment biomarker targets in specific populations.